The Effectiveness of Problem-Based Learning in Online Language Learning - Mohd Zuraimee, Wardah; Shahlee, Shakina; M. Anthony, Elizabeth (Development in Language Studies, 2022)
Online language learning is still leaning towards teacher-centred learning where learners do not have enough opportunities to demonstrate their language skills in class as they are trying to finish their syllabus. Problem-Based Learning (PBL) is the opposite of conventional learning where the knowledge input comes from the student themselves as they are trying to solve a problem given by the teacher. Hence, this study aims to investigate the use of PBL for online language learning classroom participation and the effectiveness of PBL in improving English language usage through online language learning. A survey was conducted and distributed among undergraduates taking the English for Higher Education (EHE) course in Universiti Tun Hussein Onn Malaysia (UTHM) where their perspectives on PBL were recorded and analyzed via descriptive analysis. The findings show that PBL helps in increasing students’ class participation, increase learning motivation, improve English language skills and soft skills. Hence, PBL is suitable for educators who wish to increase students’ engagement in learning, facilitate their language learning and soft skills. Future researchers should consider incorporating PBL into a variety of online English language courses or online third language courses. Apart from that, there is a need to fully comprehend the most effective trigger for eliciting the excellent efficiency from language learners, resulting in PBL becoming even more widely used.